Effectiveness of Data Visualization Training for Junior and Senior High School Teachers to Improve Scientific Article Writing Competence - Vera Maya Santi; Widyanti Rahayu; Ria Arafiyah; Faroh Ladayya; Zahrah Hashifah; Amira Basyila Sarwa; Kinanti Anindia Putri; Siti Fadilah Nurkhotimah; Ayda Syifa Ul Aliyah (Pelita Eksakta, 2026)
This community service program aims to enhance the scientific article writing competence of junior and senior high school teachers in Sukabumi Regency through training on data presentation and visualization using Microsoft Excel with the Data Analysis Add-Ins. The initiative was designed to address teachers’ limited statistical skills, low technological literacy, and challenges in processing and interpreting data for research activities. Conducted online in two sessions, the training included material delivery, software demonstrations, and pre- and post-training assessments. The results indicate a significant improvement in participants’ knowledge, as evidenced by the paired t-test yielding a p-value of 0.00. Thematic analysis of open-ended responses further revealed positive perceptions regarding the training’s relevance, clarity, and usefulness in strengthening statistical understanding. Overall, the program effectively improved teachers’ competencies in data analysis and scientific writing, while participants also expressed the need for more advanced training related to educational media and professional development